Dampak Covid-19 Terhadap Pelaku Usaha Kedai Kopi di Kota Gresik - Wahyu Ratnasari; Hendra Santoso (Jurnal Ilmiah Jendela Pendidikan, 2022)
This study aims to find out how much impact the implementation of the Java-Bali PPKM will be during the Covid-19 pandemic. Most levels of society, both from students, students, employees, and MSME business actors are also affected by the restrictions on activities carried out by the Indonesian government. Starting from teaching and learning activities and lectures that are required for online meetings at home, as well as curfews in business places and public roads. This rule finally makes business actors, especially coffee shop owners in Gresik, feel a decrease in the number of daily visitors which also has an effect on the decline in turnover. The increasingly difficult situation made business actors finally close the operation of coffee shops either temporarily or permanently. The author uses a qualitative descriptive method in observing the coffee shop business and also interviewing workers affected by PPKM in Gresik